2020
DOI: 10.3389/fphar.2020.00725
|View full text |Cite
|
Sign up to set email alerts
|

Focus on Triple-Negative Breast Cancer: Potassium Channel Expression and Clinical Correlates

Abstract: Despite improvements in early diagnosis and treatment, breast cancer is still a major health problem worldwide. Among breast cancer subtypes, the most challenging and harder to treat is represented by triple-negative molecular subtype. Due to its intrinsic features this subtype cannot be treated neither with hormonal therapy (since it does not express estrogen or progesterone receptors) nor with epidermal growth factor receptor 2 (HER2) inhibitors (as it does not express high levels of this protein). For these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…These effects take place following the interaction between TG2 and another voltage-dependent channel, Kv7, modulated by the G-protein function of TG2, as demonstrated using the specific inhibitor LDN 27129 [44]. However, Kv7 channels do not seem to have any important role in eliciting the membrane current of BC cells [40], whereas Kv10.1 is involved [75]. The expression of the Kv10.1 channel, as well as that of Orai1, which sustains Ca 2+ influx, depends on the activation of the discoidin domain receptor 1 pathway, which is mediated by collagen type I and activated via ERK1/2 [76,77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects take place following the interaction between TG2 and another voltage-dependent channel, Kv7, modulated by the G-protein function of TG2, as demonstrated using the specific inhibitor LDN 27129 [44]. However, Kv7 channels do not seem to have any important role in eliciting the membrane current of BC cells [40], whereas Kv10.1 is involved [75]. The expression of the Kv10.1 channel, as well as that of Orai1, which sustains Ca 2+ influx, depends on the activation of the discoidin domain receptor 1 pathway, which is mediated by collagen type I and activated via ERK1/2 [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, K + channels have a leading role and represent good candidates as markers. They are easily druggable, owing to their position on the cell membrane [40]. The voltage-dependent Kv10.1 channel (also named ether à-go-go-1, Eag1) has been indicated as a good target for therapy of most human tumors [41], despite its similar structure to the Kv11.1 channel (human ether-à-go-go-related gene, hERG), which is relevant for cardiac physiology.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports that the potassium ions that are dependent on their level might play an important role in breast cancer onset. Lastraioli E. reported on 1.3 voltage-gated potassium ion channels (KV channels), the overexpression of which could correlate with the progression of breast cancer [248]. It has been demonstrated that the KV 1.3 channels are linked to a bad prognosis in patients with breast cancer.…”
Section: Potassiummentioning
confidence: 99%
“…Other potassium channels, such as the voltage-gated potassium channels, are highly expressed in ductal pancreas adenocarcinoma (PDAC), and their blockade could be a useful therapeutic strategy to be added to conventional therapy [218]. Also in breast cancer, in particular the triple-negative type, it has been seen that the expression of potassium channels determines increased in vitro invasion, tumor growth in vivo, and metastases, so it is interesting to reposition already approved potassium channel-blocking drugs for the therapy of this type of particularly aggressive cancer [219,220]. In breast cancer, the expression of potassium channel subfamily K member 6 (K 2P 6.1) is also increased, which enhances the proliferation, invasion, and migratory capacity of cancer cells.…”
Section: Pharmacological Modulation Of Potassium Channels In Cancermentioning
confidence: 99%